Antimicrobial resistance of Helicobacter pylori strains to five antibiotics, including levofloxacin, in Northwestern Turkey - Caliskan,Reyhan (2015)
INTRODUCTION: Antibiotic resistance is the main factor that affects the efficacy of current therapeutic regimens against Helicobacter pylori. This study aimed to determine the rates of resistance to efficacy clarithromycin, amoxicillin, tetracycline, levofloxacin and metronidazole among H. pylori strains isolated from Turkish patients with dyspepsia. METHODS: H. pylori was cultured from corpus and antrum biopsies that were collected from patients with dyspeptic symptoms, and the antimicrobial susceptibility of H. pylori was determined using the E-test (clarithromycin, amoxicillin, tetracycline, metronidazole and levofloxacin) according to the EUCAST breakpoints. Point mutations in the 23S rRNA gene of clarithromycin-resistant strains were investigated using real-time PCR. RESULTS: A total of 98 H. pylori strains were isolated, all of which were susceptible to amoxicillin and tetracycline. Of these strains, 36.7% (36/98) were resistant to clarithromycin, 35.5% (34/98) were resistant to metronidazole, and 29.5% (29/98) were resistant to levofloxacin. Multiple resistance was detected in 19.3% of the isolates. The A2143G and A2144G point mutations in the 23S rRNA-encoding gene were found in all 36 (100%) of the clarithromycin-resistant strains. Additionally, the levofloxacin MIC values increased to 32 mg/L in our H. pylori strains. Finally, among the clarithromycin-resistant strains, 27.2% were resistant to levofloxacin, and 45.4% were resistant to metronidazole. CONCLUSIONS: We conclude that treatment failure after clarithromycin- or levofloxacin-based triple therapy is not surprising and that metronidazole is not a reliable agent for the eradication of H. pylori infection in Turkey.